Epic Interpretations of the Image of Trees in Uzbek Folk Tales - Rustamova Gavkhar Bahronovna (International Journal on Integrated Education, 2021)
It is known that in Uzbek folk tales there are many figurative trees such as maple, mulberry, poplar, walnut. In the plot of fairy tales, real events are expressed in a way consistent with extraordinary events and magical motifs, in which the trees are interpreted as the foundation, the core, the pillar of the world and the way that unites the worlds. This article also contains epic interpretations related to the image of trees in folk tales.